Effects of Adding Dietary Fenugreek (Trigonella foenum graecum L.) Powder on Productive Performance and Egg Quality of Laying Hens - Al Aqil , Abdul-Aziz A. (International Journal of Poultry Science, 2016)
The present study was conducted to evaluate the effect of adding different dietary levels of fenugreek (0.0, 0.1, 0.2 and 0.4%) powder on productive performance and egg quality of laying hens from 52 to 60 weeks of age. Two hundred 52-week old Hisex laying hens were randomly distributed in four dietary treatments with ten replicates with five hens per each replicate. Body weight gain, egg production, feed consumption, feed conversion ratio, egg weight, egg mass, egg specific gravity, Haugh units and egg yolk color were measured. Results obtained from the present study showed that no significant differences were observed in body weight gain, egg production, egg weight, egg specific gravity, egg yolk color and Haugh unit by adding 0.0, 0.1, 0.2, or 0.4% dietary levels of fenugreek powder. Feed consumption of hens fed with diets containing 0.4% decreased significantly compared with those fed diets containing 0.0, 0.1 and 0.2% dietary levels of fenugreek powder. However, hens fed diets containing 0.1, 0.2 and 0.4% fenugreek powder showed lower (better) feed conversion ratio and lower egg mass than those fed diets containing 0.0% fenugreek powder. It was concluded that adding dietary fenugreek powder at the level of 0.4% had some positive effects on productive performance and egg quality of laying hens from 52 to 60 weeks of age.